Agile Processes in Software Engineering and Extreme Programming 18th International Conference, XP 2017, Cologne, Germany, May 22-26, 2017, Proceedings - Baumeister, Hubert; Lichter, Horst; Riebisch, Matthias (Lecture Notes in Business Information Processing, 2017)
This book is open access under a CC BY license. The volume constitutes the proceedings of the 18th International Conference on Agile Software Development, XP 2017, held in Cologne, Germany, in May 2017. The 14 full and 6 short papers presented in this volume were carefully reviewed and selected from 46 submissions. They were organized in topical sections named: improving agile processes; agile in organization; and safety critical software. In addition, the volume contains 3 doctoral symposium papers (from 4 papers submitted). .